2017
DOI: 10.15566/cjgh.v4i2.130
|View full text |Cite
|
Sign up to set email alerts
|

Family planning and reproductive health supply stockouts: problems and remedies for faith-based health facilities in Africa

Abstract: Background and aims: Faith-based organizations (FBOs) provide a substantial portion of the health care services in many African countries. FBO facilities do consider family planning and reproductive health services as essential to reducing maternal and child mortality, and to the growth of healthy families. Many health facilities, however, struggle to maintain adequate stocks of reproductive health (RH) supplies because of the various RH supply chains and funding sources, which often operate separately from ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Procuring family planning commodities was a recurring challenge for this project and is a common problem across Africa, especially for FBO-managed facilities 18 . A study of FBO-managed facilities in 13 African countries found that more than half had faced stock-outs of one or more reproductive health products (including contraceptives) in the past 3 months, requiring staff to implement creative solutions such as finding other sources of commodities and purchasing and storing buffer stock 19 . The CHAK project adopted such strategies, procuring buffer stocks of contraceptives (particularly IUDs and implants) in both Phase 1 and Phase 2 of the project to ensure that lack of commodities would not limit performance.…”
Section: Discussionmentioning
confidence: 99%
“…Procuring family planning commodities was a recurring challenge for this project and is a common problem across Africa, especially for FBO-managed facilities 18 . A study of FBO-managed facilities in 13 African countries found that more than half had faced stock-outs of one or more reproductive health products (including contraceptives) in the past 3 months, requiring staff to implement creative solutions such as finding other sources of commodities and purchasing and storing buffer stock 19 . The CHAK project adopted such strategies, procuring buffer stocks of contraceptives (particularly IUDs and implants) in both Phase 1 and Phase 2 of the project to ensure that lack of commodities would not limit performance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more severe cases of stockouts might have been identified if all the facilities assessed kept a record of stockouts of FP commodities. Other studies have reported stockout of essential medicines in the Nigerian supply chain system 29,30 and the burden this puts on the healthcare system is well established including reduction in the utilization of public healthcare services, increased distrust in healthcare service providers, reduced medication adherence, increase in the burden of disease and failure to meet program targets 31 . To address one of the main issues that affect the use of FP commodities and services, which is stockouts of commodities, it may be imperative to digitalize FP commodity supply chain functions across all levels to aid data gathering for informed decision making.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, model programs were discussed, while others provided empirical analysis of practices and attitudes. [11][12][13][14][15][16][17] Each advocated, to greater or lesser degrees, for the expansion of family planning services and solutions. Given their focus on operational concerns, for the most part these papers did not examine the theological or ethical justifications for expansion.…”
mentioning
confidence: 99%